Multisensory Experiences of Italian Tourists in Rural Transylvania - Sandru, Codrina; Nechita, Florin (Niccolo Cusano University-Rome Symphonya Emerging Issues in Management, 2017)
The concept of experiential tourism is a foundation for the valorisation of intangible cultural heritage of a rural area from south-eastern Transylvania, Romania. The experience was closely observed and analysed in order to determine how the regional tourism promotion organizations should use intangible heritage assets in order to promote this area, and also to be incorporated in the tourist offers by Romanian tour operators. Aiming to evaluate tourists’ insights on their rural tourism experience, a close research was conducted among the participants at an international summer school, specially designed for the valorisation of the intangible cultural heritage. The results outline the sensorial triggers, which describe Italian tourists’ experience in Fagaras Land.
Keywords: global tourism; rural tourism; intangible heritage; tourist experience; multisensory experience; Transylvania; Fagaras Land; destination marketing